Aesthetic Considerations for Automated Platformer Design - Cook, Michael; Colton, Simon; Pease, Alison (Proceedings of the AAAI Conference on Artificial Intelligence and Interactive Digital Entertainment, 2012)
We describe ANGELINA3, a system that can automatically develop games along a defined theme, by selecting appropriate multimedia content from a variety of sources and incorporating it into a game’s design. We discuss these capabilities in the context of the FACE model for assessing progress in the building of creative systems, and discuss how ANGELINA3 can be improved through further work.